2018
DOI: 10.1007/s10792-018-0840-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk factors associated with intraoperative floppy iris syndrome: a prospective study

Abstract: The findings suggest that finasteride use and aging are risk factors for IFIS and confirm the association of tamsulosin use with IFIS. Further, doxazosin appears to be a relatively safe drug with respect to the occurrence of IFIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
1
24
0
1
Order By: Relevance
“…8 In addition, several neuromodulators including benzodiazepines, donepezil and duloxetine have been associated with IFIS by several studies. 5,7,33,34 In a large retrospective study, Chatziralli et al reported an increased incidence of IFIS in patients receiving benzodiazepines, an association that was confirmed in a univariate analysis by Kaczmarek et al 5,7 In 2007 Papadopoulos et al reported IFIS in a patient with long history (8 years) of donepezil intake for Alzheimer's disease, while recently González-Martín -Moro et al published a case of IFIS in a patient receiving duloxetine as antidepressant for 3 years. 33,34 The increased incidence of IFIS in patients treated with the abovementioned medications might be either causative or coincidental.…”
Section: Other Drugsmentioning
confidence: 95%
See 4 more Smart Citations
“…8 In addition, several neuromodulators including benzodiazepines, donepezil and duloxetine have been associated with IFIS by several studies. 5,7,33,34 In a large retrospective study, Chatziralli et al reported an increased incidence of IFIS in patients receiving benzodiazepines, an association that was confirmed in a univariate analysis by Kaczmarek et al 5,7 In 2007 Papadopoulos et al reported IFIS in a patient with long history (8 years) of donepezil intake for Alzheimer's disease, while recently González-Martín -Moro et al published a case of IFIS in a patient receiving duloxetine as antidepressant for 3 years. 33,34 The increased incidence of IFIS in patients treated with the abovementioned medications might be either causative or coincidental.…”
Section: Other Drugsmentioning
confidence: 95%
“…The appearance of intraoperative floppy iris syndrome has been shown to be affected by many reasons and various systemic medications. [5][6][7][8][9][10] However, IFIS came in the spotlight when the therapeutic algorithm for the treatment of benign prostatic hyperplasia (BPH) suggested the intake of a1-ARA as the first line treatment, substituting surgical intervention. 13 Three subtypes of a1-adrenergic receptors (a1-AR) have been identified so far: a1 A , a1 B and a1 D .…”
Section: Pathogenetic Mechanismmentioning
confidence: 99%
See 3 more Smart Citations